Roles of tumor necrosis factor-like ligand 1A in γδT-cell activation and psoriasis pathogenesis - Wang, Shangyi; Kozai, Mina; Hiraishi, Masaya; Rubel, Md. Zahir Uddin; Ichii, Osamu; Inaba, Mutsumi; Matsuo, Kazuhiro; Takada, Kensuke (Frontiers in Immunology, 2024)
Background: Interleukin (IL)-17-producing gdT (gdT17) cells mediate inflammatory responses in barrier tissues. Dysregulated gdT17 cell activation can lead to the overproduction of IL-17 and IL-22 and the development of inflammatory diseases, including psoriasis. IL-23 and IL-1β are known to synergistically activate gdT17 cells, but the regulatory mechanisms of gdT17 cells have not been fully elucidated. This study aimed to reveal the contribution of the inflammatory cytokine tumor necrosis factor-like ligand 1A (TL1A) to gdT17 cell activation and psoriasis development.Methods: Anti-TL1A antibody was injected into an imiquimod (IMQ)-induced murine psoriasis model. TL1A receptor expression was analyzed in splenic and dermal gdT cells. gdT cells were tested for cytokine production in vitro and in vivo under stimulation with IL-23, IL-1β, and TL1A. TL1A was applied to a psoriasis model induced by intradermal IL-23 injection. Mice deficient in gdT cells were intradermally injected with IL-23 plus TL1A to verify the contribution of TL1A-dependent gdT-cell activation to psoriasis development.Results: Neutralization of TL1A attenuated gdT17 cell activation in IMQ-treated skin. TL1A induced cytokine production by splenic gdT17 cells in synergy with IL-23. Dermal gdT17 cells constitutively expressed a TL1A receptor at high levels and vigorously produced IL-22 upon intradermal IL-23 and TL1A injection but not IL-23 alone. TL1A exacerbated the dermal symptoms induced by IL-23 injection in wild-type but not in gdT cell-deficient mice.These findings suggest a novel regulatory mechanism of gdT cells through TL1A and its involvement in psoriasis pathogenesis as a possible therapeutic target.